2022
DOI: 10.1002/pro.4534
|View full text |Cite
|
Sign up to set email alerts
|

Active site architecture of coproporphyrin ferrochelatase with its physiological substrate coproporphyrin III: Propionate interactions and porphyrin core deformation

Abstract: Coproporphyrin ferrochelatases (CpfCs) are enzymes catalyzing the penultimate step in the coproporphyrin-dependent (CPD) heme biosynthesis pathway, which is mainly utilized by monoderm bacteria. Ferrochelatases insert ferrous iron into a porphyrin macrocycle and have been studied for many decades, nevertheless many mechanistic questions remain unanswered to date. Especially CpfCs, which are found in the CPD pathway, are currently in the spotlight of research. This pathway was identified in 2015 and revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 79 publications
2
29
0
Order By: Relevance
“…The experiment allowed us to verify that Lm CpfC is active in its crystalline state, even though reaction kinetics presumably are slowed down compared to in‐solution approaches (Schmidt, 2020; Schmidt & Saldin, 2014), due to limited mass exchange rate. The overall structures of the “24%” (soaking time: 2 min), “34%” (soaking time: 3 min), and “68%” (soaking time: 4 min) iron occupancy samples are identical to those of Lm CpfC‐cpIII (PDB ID: http://firstglance.jmol.org/fg.htm?mol=8AT8) (Dali et al, 2023) and Lm CpfC‐coproheme (PDB ID: http://firstglance.jmol.org/fg.htm?mol=6SV3) (Hofbauer et al, 2020). In fact, their secondary structural elements are perfectly superimposable: the “24% Fe” structure shows an rmsd‐value of the backbone carbons compared to the Lm CpfC‐cpIII structure of 0.311 Å and 0.328 Å when aligned with the Lm CpfC‐coproheme structure; the “34% Fe” structure shows rmsd‐values of 0.165 Å (compared to Lm CpfC‐cpIII) and 0.186 Å (compared to Lm CpfC‐coproheme); the “68% Fe” structure shows rmsd‐values of 0.164 Å (compared to Lm CpfC‐cpIII) and 0.183 Å (compared to Lm CpfC‐coproheme).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The experiment allowed us to verify that Lm CpfC is active in its crystalline state, even though reaction kinetics presumably are slowed down compared to in‐solution approaches (Schmidt, 2020; Schmidt & Saldin, 2014), due to limited mass exchange rate. The overall structures of the “24%” (soaking time: 2 min), “34%” (soaking time: 3 min), and “68%” (soaking time: 4 min) iron occupancy samples are identical to those of Lm CpfC‐cpIII (PDB ID: http://firstglance.jmol.org/fg.htm?mol=8AT8) (Dali et al, 2023) and Lm CpfC‐coproheme (PDB ID: http://firstglance.jmol.org/fg.htm?mol=6SV3) (Hofbauer et al, 2020). In fact, their secondary structural elements are perfectly superimposable: the “24% Fe” structure shows an rmsd‐value of the backbone carbons compared to the Lm CpfC‐cpIII structure of 0.311 Å and 0.328 Å when aligned with the Lm CpfC‐coproheme structure; the “34% Fe” structure shows rmsd‐values of 0.165 Å (compared to Lm CpfC‐cpIII) and 0.186 Å (compared to Lm CpfC‐coproheme); the “68% Fe” structure shows rmsd‐values of 0.164 Å (compared to Lm CpfC‐cpIII) and 0.183 Å (compared to Lm CpfC‐coproheme).…”
Section: Resultsmentioning
confidence: 99%
“…In regard to the R29-p7 H-bond interaction, it has been already observed that this H-bond is not always present, since in the LmCpfC-cpIII crystal structure the R29 residue shows two possible conformations, in and out (Figure 2b and Dali et al, 2023). In solution, the R29L variant shows wild-type-like characteristics upon coproheme binding, while upon cpIII binding it shares similarities with the R45L variant, where only the H-bond with p6 is removed (Dali et al, 2023;Gabler et al, 2022). In this work, changes in the orientation of the R29 residue are observed along the metalation process.…”
Section: Iron Insertion Followed By X-ray Crystallographymentioning
confidence: 95%
See 1 more Smart Citation
“…The reason for the reduced activity of the ppIXbound WT and the complete loss of activity of its key distal variants is very likely to derive from an incorrect substrate binding, as a consequence of the presence of only two propionate substituents in the substrates. In fact, comparison of the structures, functional and spectroscopic studies of WT and mutated CpfCs from Bacillus subtilis in complex with N-MeMP or deuteroporphyrin IX 2,4-disulfonic acid dihydrochloride [15,35] with those of LmCpfC with coproheme and coproporphyrin III [5][6][7], clearly shows that the interaction of propionates at positions 2 and 4 with residues well buried in the protein core is fundamental for correct binding. The complete ferrous iron insertion also observed in this work by cpIbound WT strengthens this conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Ferrochelatases are enzymes which insert ferrous iron into a porphyrin macrocycle within heme biosynthesis pathways [4]. However, while ferrochelatases of monoderm and diderm representatives do not significantly differ from each other in their overall subunit structure and fold, they exhibit differences in the porphyrin binding site architecture [5][6][7]. In addition, in some ferrochelatase representatives of both monoderm and diderm bacteria (e.g., in some actinobacterial ferrochelatases or representatives of Bacteroidetes [8]), a [2Fe-2S] cluster of yet unknown function is found.…”
Section: Introductionmentioning
confidence: 99%